PENGARUH PELATIHAN KESELAMATAN PASIEN TERHADAP PEMAHAMAN PERAWAT PELAKSANA MENGENAI PENERAPAN KESELAMATAN PASIEN DI RSI SITTI MARYAM MANADO - Suwandi I. Luneto (Universitas Muhammadiyah Manado, 2017)
Patient safety was to reduce and relieve measures that not secured within health services system as best as possible through the use of the appearance of good practice in order to optimize the patient outcome .The same with this hughes ( 2008 ) said that patient safety is the prevention of injured towards patientsThe purpose of this research to know the influence of training patient safety to understanding nurse implementing regarding the application of patient safety in the hospital . The research was done by adopting quantitative with the design quasi experiment .Sample made on the number of respondents as many as 35 people by adopting one group pretest-posttest designData collection was carried out by means of a questionnaire .Furthermore the data him the mixed with both assistance program version computer spss 20 for analysis by test statistics samples test paired with a kemaaknaan ( α = 0,05 ) .Results showed that obtained the female sex terbayak the research is 21 respondents ( 60.0 % ) . Conclusions in this research is the training patient safety of understanding implementing nurse regarding the implementation of the patient safety P = 0,000, the p is smaller than the α = 0.05